2019
DOI: 10.1097/ccm.0000000000003520
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Propofol and Dexmedetomidine Sedation on Norepinephrine Requirements in Septic Shock Patients: A Crossover Trial

Abstract: Objectives: Propofol-based sedation may increase hemodynamic instability by decreasing vascular tone and venous return. Incremental exogenous catecholamines doses may be required to counteract such effects, aggravating the deleterious effects of sympathetic overstimulation. α-2 adrenergic agonists have been reported to decrease norepinephrine requirements in experimental septic shock. The aim of the present study is to test the hypothesis that switching from sedation with propofol to the α-2 agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 34 publications
2
66
0
Order By: Relevance
“…As alpha-2 agonist, dexmedetomidine may increase the risk of hypotension and bradycardia [14,15] and, in patients with septic shock, this may be both dangerous and harmful. However, experimental data also suggest that dexmedetomidine can be administered in septic shock and may even have catecholamine-sparing effects [5,[16][17][18][19][20][21]. Our findings are consistent with such experimental observations.…”
Section: Discussionsupporting
confidence: 90%
“…As alpha-2 agonist, dexmedetomidine may increase the risk of hypotension and bradycardia [14,15] and, in patients with septic shock, this may be both dangerous and harmful. However, experimental data also suggest that dexmedetomidine can be administered in septic shock and may even have catecholamine-sparing effects [5,[16][17][18][19][20][21]. Our findings are consistent with such experimental observations.…”
Section: Discussionsupporting
confidence: 90%
“…However, DEX seems promising in this context, and mechanistic, pharmacodynamic, and pharmacokinetic studies with DEX in critical septic patients have increased in recent years. Recent evidence in septic shock sedated patients have shown that for a comparable level of sedation, switching from propofol to dexmedetomidine resulted in a reduction of norepinephrine requirements in septic shock patients (Morelli et al, 2019). Table 3 shows the benefits of adding DEX in different clinical settings.…”
Section: Dex and Sepsismentioning
confidence: 99%
“…Potential neuroprotection in Ischemic brain injury Ren et al, 2016;Alam et al, 2017;Sottas, 2017;Schomer et al, 2019 Sepsis Anti-inflamatory effects in sepsis. Potential hemodynamic stability Xiang et al, 2014;Morelli et al, 2019 AUTHOR CONTRIBUTIONS RC: designed the manuscript and the structure of the themes and wrote about animal models and basic targets of DEX. MI and IC: wrote about human pharmacokinetics of DEX.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…17,18 Currently, DEX is not recommended as a standard-of-care sedative due to its central action to inhibit sympathetic nerve activity, 19,20 which would be expected to reduce blood pressure in sepsis. However, in both clinical [21][22][23] and experimental 19,24,25 sepsis, there is evidence that treatment with a 2 -adrenergic receptor agonists improves responsiveness to exogenous vasopressors such as norepinephrine, phenylephrine, and angiotensin II, which likely accounts for their ability to preserve blood pressure. A multinational, doubleblinded, randomized clinical trial is currently assessing DEX as a primary sedative agent, 26 making this agent of clinical interest and relevance.…”
Section: Translational Statementmentioning
confidence: 99%